2009
DOI: 10.1039/b820224a
|View full text |Cite
|
Sign up to set email alerts
|

A metabonomic study of hepatitis B-induced liver cirrhosis and hepatocellular carcinoma by using RP-LC and HILIC coupled with mass spectrometry

Abstract: Liver cirrhosis and hepatocellular carcinoma (HCC) are fatal sequelaes of chronic hepatitis B in China. The sera from HCC and cirrhosis were profiled by rapid resolution liquid chromatography coupled with quadrupole time-of-flight (Q-TOF) mass spectrometry. Reversed-phased (RP) liquid chromatography and hydrophilic interaction chromatography (HILIC) were used for the data acquisition. The normalized and combined data were handled by chemometric analysis, and the combination proved to be effective and reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 206 publications
(213 citation statements)
references
References 44 publications
13
199
1
Order By: Relevance
“…4A). Findings from serum metabonomics partially ascertained the previous report that FFAs would increase in RA individuals [20,21]. A report indicated that fasting-associated increases in total plasma FFAs promoted lymphocyte proliferation in vitro and might not facilitate to alleviate inflammation [22].…”
Section: Effect Of Ynb On the Down-stream Metabolism Of Aa In Osteoblmentioning
confidence: 52%
“…4A). Findings from serum metabonomics partially ascertained the previous report that FFAs would increase in RA individuals [20,21]. A report indicated that fasting-associated increases in total plasma FFAs promoted lymphocyte proliferation in vitro and might not facilitate to alleviate inflammation [22].…”
Section: Effect Of Ynb On the Down-stream Metabolism Of Aa In Osteoblmentioning
confidence: 52%
“…And also, some important serum metabolites have been found altered in HCC and CIR involved in lipid metabolism, increased protein degradation, perturbations of the tricarboxylic acid (TCA) cycle [16]. Importantly, when comparing the serum metabolic changes of CIR and HCC in our previous study, we found not only several differential metabolites specific to CIR and HCC but also different metabolic correlation networks [17].…”
Section: Introductionmentioning
confidence: 99%
“…The ion source temperature was set at 300°C and other parameters were set as our previous protocol [17]. The mass accuracy was calibrated before analysis and a real-time calibration of mass accuracy was implemented to ensure the stability of mass accuracy.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…Many metabolomic studies have focused on the early diagnosis of HCC, especially the discrimination between HCC and its precancerous lesion of liver cirrhosis, which causes a wide diversity of metabolic disorders. To identify HCC-specific metabolites, a visualized method of the shared and unique structure was applied to the analysis of metabolome data [58]. Even small tumors can change metabolic profiles, regardless of the appearance of cirrhosis lesions in the liver.…”
Section: Primary Liver Cancermentioning
confidence: 99%